A UTILIZAÇÃO DE “SERIOUS GAMES” COMO FERRAMENTAS EDUCACIONAIS EM ENDODONTIA. - AZEVEDO, Izabelle Maria Cabral de (2018)
Scientific and technological development is a subject of change in several areas, including in the health sector. Within the context, the games Serious Games, that are inserted in the educational area appeared. An Educational Electronic Game for pedagogical practice can provide new concepts of teaching-learning in an interactive environment stimulating memory and concentration. Both games and simulators are widely used in health education. In teaching hospitals, for example, students simulate situations with colleagues and patients in addition to practicing their clinical skills. In dentistry there are few reports about the use of serious games to aid learning. The teaching of the Endodontics specialty should prepare the future professional for the accomplishment of endodontic procedures, emergency procedures, prescription of medicines and mainly obtaining correct diagnoses, guaranteeing the autonomy of the dental surgeon in his work environment. Thus, the purpose of this thesis was to observe what we had on this topic related to serious games, build an educational game in the area and apply it with students of the last year of graduation in Dentistry. The first chapter we decided to build a quiz game that tests the knowledge already acquired, validating technically and pedagogically the issues used in the issue of Endodontic Emergencies. The game is now available on the Android platform for download. In the second chapter we applied the game to students of the last year of graduation to evaluate through a questionnaire based on EGameFlow if a serious game can be used as a tool to improve knowledge. Through this we could observe that all the contemplated categories were evaluated positively, mainly those related to the improvement of knowledge. From this initiative, the perspective of serious games approach appears on a larger scale, since its use has been highlighted by its potential of reach and social impact.